Treatment of Thoracolumbar Spinal Infections through Anterolateral Approaches Using Expandable Titanium Mesh Cage for Spine Reconstruction - Tarantino Roberto; Marruzzo Daniele; Cappelletti Martina; De Giacomo Tiziano; Delfini Roberto (The Scientific World Journal)
Pyogenic vertebral osteomyelitis (PVO) is still a rare pathology. However, its incidence is on the rise. This is due to an increasing population with predisposing factors. Also, the availability of more effective diagnostic tools has brought it increasingly to the surgeon’s attention. In this study the patients were treated in the Neurosurgery Division of the Department of Neurological Sciences and Psychiatry of the Sapienza University of Rome, between 2001 and 2009. They had thoracolumbar pyogenic spondylitis. This study was undertaken in order to identify the correct diagnostic and therapeutic treatment needed in such cases. From the cases studied here, it is evident that spinal infections can be extremely insidious and that diagnosis tends to be reached late. Surgery, along with the antibiotic treatment, allows for eradication of the causes of the pathology by the reclamation of the affected region. Surgery is also fundamental in helping to recover vital functions and in restoring as much as possible the correct curvature of the rachises. The use of an anterolateral approach is dictated by the necessity of obtaining 360° stability as well as by the need to clear away extensive infections, which are not always reachable using a posterior approach.